PENGARUH PEMANFAATAN SISTEM INFORMASI AKUNTANSI, KOMPETENSI SUMBER DAYA MANUSIA DAN PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Fajriati, Unun Rizka; Maghfiroh, Siti; sugiarto, sugiarto (Soedirman Accounting, Auditing and Public Sector Journal, 2024)
This research is a quantitative research with survey method. This research takes the title: "The Influence of Accounting Information Systems, Human Resource Competence and Internal Control on the Quality of Local Government Financial Reports", an empirical study in Kebumen Regency and Banyumas Regency. The purpose of this study was to determine the effect of Accounting Information Systems, Human Resources Competence and Internal Control on the Quality of Local Government Financial Reports. The population in this study were OPD in Kebumen and Banyumas districts, each of which consisted of 17 (seventeen) districts. The number of respondents in this study were 102 respondents. The sampling technique used was purposive sampling method. Data was collected by distributing questionnaires to the finance department employees. Data analysis was performed using the SPSS (Statistical Package for the Social Sciences) application. The results of data analysis in this study indicate that: (1) The accounting information system has a significant effect on the quality of local government financial reports. (2) The competence of human resources has a significant effect on the quality of local government financial reports. (3) Internal control does not affect the quality of local government financial reports. The implication of the conclusion above is that local governments in improving the quality of financial reports can pay attention to influencing factors, this study proves that the quality of local government financial reports is influenced by accounting information systems and human resource competencies